IDDF2018-ABS-0124 Identification of MIR-148A in plasma as a potential noninvasive biomarker for hepatocellular carcinoma. (June 2018) - Han, Juqiang; Li, Jiarui; Liu, Wenpeng; Liang, Jiguang; Huang, Zhigang; Wang, Shuai; Zhao, Caiyan; Xu, Xiaojie; Ye, Qinong
Abstract : Background: Detection of microRNA (miRNA) aberrations in the peripheral plasma is a new approach for hepatocellular carcinoma (HCC) screening. The aim of this study was to characterise miR-148a in the peripheral plasma as a non-invasive biomarker for diagnosis of HCC. Methods: Plasma-based miR148a analysis was performed on 346 plasma samples, including 155 HCCs, 96 liver cirrhosis and 95 healthy controls by using quantitative Real-Time PCR (qRT-PCR). Subsequently, plasma-based miR148a levels were validated in 97 pairs of HCC followed-up after removal of the primary tumour. Finally, Receiver operating characteristics (ROC) curves were generated to confirm predicting the value of plasma-based miR148a in HCC. Results: Plasma-based miR-148a expression was significantly lower in 155HCCs compared to 96 liver cirrhosis (p<0.01) as well as 95 healthy control (p<0.01). Upon removal of the primary HCC tumour, levels of plasma-based miR-48aincreased significantly compared with their initial levels (p<0.0001). The area under receiver operating characteristic (AUROC) curve for plasma-based miR-148a was 0.919, with a sensitivity of 89.6% and specificity of 89.0% for HCC patients compared with liver cirrhosis. In HCC with negative or less expressing AFP, the AUROC values of plasma-based miR148a were 0.949 with a sensitivity of 90.6% and specificity of 92.6%. Conclusions: Plasma-based miR-148a can be applied as a potential non-invasive biomarker for HCC screening, especially for HCC with negative or less expressing AFP, which can make up AFP deficiency in predicting HCC occurrence. Notes: This project was funded by Application Project of Clinical Features in Capital City (Z141107002514507).